Transvaginal ultrasound and magnetic resonance imaging in detecting rectosigmoid deep infiltrating endometriosis: a comparative meta-analysis - Xu, Ziwei; Li, Yisheng; Wang, Yingying; Wan, Yiting; Chen, Jing (Frontiers in Medicine, 2025)
ObjectiveThis meta-analysis aimed to assess the diagnostic efficacy of transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) for the detection of rectosigmoid deep infiltrating endometriosis (DIE).MethodsA thorough systematic review was performed by searching the PubMed and Embase databases for studies evaluating the diagnostic performance of TVS and MRI in rectosigmoid DIE, up until August 12, 2024. The DerSimonian and Laird approach was utilized to calculate sensitivity and specificity, with the Freeman-Tukey double arcsine transformation employed for data analysis. The quality of the included studies was evaluated using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool.ResultsThe meta-analysis encompassed 10 studies involving 1,604 patients. The findings revealed that TVS had an overall sensitivity of 0.85 (95% CI: 0.76–0.92) and specificity of 0.92 (95% CI: 0.85–0.98), while MRI demonstrated a sensitivity of 0.83 (95% CI: 0.73–0.92) and specificity of 0.95 (95% CI: 0.90–0.99). Statistical analysis indicated no significant differences in sensitivity (p = 0.86) or specificity (p = 0.50) between the two imaging techniques. Additionally, the funnel plot asymmetry test did not reveal significant publication bias for any outcomes (Egger’s test: all p > 0.05).ConclusionThe meta-analysis reveals nearly equivalent diagnostic performance of TVS and MRI in detecting rectosigmoid DIE, with no statistical differences in sensitivity and specificity. However, high heterogeneity among studies highlights the need for further prospective research.Systematic review registrationThe protocol for this meta-analysis has been registered with the International Prospective Register of Systematic Reviews (PROSPERO) under the ID: CRD42024559141, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024559141.